Development of an ontology for a multi-agent system controlling a production line - Rodrigues, Nelson (2013)
Nowadays, the industry is very demanding in terms of customized high quality products at lower costs. Furthermore, the customers intention of having the product as soon as possible, and companies having the restriction of time, which in this case is a crucial variable, also increases the nal product cost. For this reason, it becomes unacceptable the development of solutions based on centralized implementations, which do not provide robustness, exibility and recon gurability. Therefore, the implementation of multi-agent based solutions ful l the described requirements leading to a more exible, robust and agile system. This work presents the development of an important issue concerning the cooperation between the distributed agents, since one of them only has a partial view of the system. In this way the ontologies are crucial to guarantee a common structure of the knowledge exchanged among the agents. The objective of this work is the development of an ontology integrating process and quality levels to be used to represent the knowledge exchanged in a multi-agent system solution for a production line producing washing machines. Consequently, the agents exchanging shared knowledge will support better and more accurate decisions. The contribution of this work comprises the implementation of a multi-agent system, the appropriate ontology formulation as well as its implementation, which makes the integration of an industrial production line more versatile and more customized. Naturally, with this project, it is created a recon gurable and highly interoperable system. Hoje em dia, a indústria é muito exigente em termos de produtos personalizados de alta qualidade a custos baixos. Além disso, a intenção dos clientes é ter o produto logo que possível, assim as empresas têm uma limitação de tempo, que neste caso é uma variável importante, também aumenta o custo do produto nal. Por esta razão, torna-se inaceitável o desenvolvimento de soluções baseadas em implementa ções centralizadas, que não proporcionam a exibilidade, robustez e recon gurabilidade. Portanto, a implementação de soluções baseadas em multi-agente cumprem os requisitos descritos levando a um sistema mais exível, robusto e ágil. Este trabalho representa o desenvolvimento de uma questão importante relativa à coopera ção entre os agentes distribuídos, uma vez que apenas um deles tem uma visão parcial do sistema. Desta forma, as ontologias são cruciais para garantir uma estrutura comum de conhecimento trocadas entre os agentes. O objectivo deste trabalho é o desenvolvimento de uma ontologia da integração de processos e qualidade a serem utilizados para representar o conhecimento trocado em uma solução de sistema multi-agente para uma linha de produção de máquinas de lavar. Consequentemente, os agentes trocam conhecimento compartilhado que irão suportar decisões melhores e mais precisas. A contribuição deste trabalho consiste na implementação de um sistema multi-agente, a adequada formulação da ontologia, bem como a sua implementação, o que torna a integração de uma linha de produção industrial mais versátil e mais personalizada. Naturalmente, com este projecto, é criado um sistema recon gurável e altamente interoperável.